Influence of carboxyl functionalized MWCNT loading on the thermal stability and long-term water uptake behavior in tri-layered jute FRCs - B.M. Saif; Hassan Tawsif Tazwar; Maisha Farzana Antora; Debanan Bhadra (Results in Engineering)
Investigations on the influence of carboxyl functionalized MWCNTs on epoxy composites solely reinforced by jute fiber are very scarce. Therefore, an attempt has been made to analyze the long-term moisture absorption behavior and thermal stability at the high-temperature range (30 °C-1200 °C) in jute FRC filled with varying amounts of functionalized MWCNTs (wt. %). Jute fibers derived from needle-punched jute mats were chemically pre-treated and were studied using Fourier Transform Infrared Spectroscopy (FT-IR). The MWCNTs were ultrasonicated to ensure uniform dispersion in the epoxy matrix. Scanning Electron Microscopy (SEM) was performed to observe the fiber, matrix, and filler interactions. As the composites were fabricated using the hand layup technique, air bubbles got entrapped into the specimens for which the void content was also reported. At a substantial saturation state (weight change <5 mg), the composite with 1 % MWCNT absorbed the most water. However, at higher CNT loadings, MWCNT agglomeration stopped water uptake. These results suggest that careful adjustment of MWCNT loading is necessary to balance hydrophilicity and porosity, thereby fine-tuning the water absorption of jute FRC. Thermogravimetric analysis (TGA) has been used in the study to assess the thermal behavior of the composites, indicating that adding MWCNTs at about 1 wt. % CNT loading can increase the thermal stability of jute fiber composites. An elevated concentration of CNTs facilitates agglomeration, impeding moisture absorption, whereas the incorporation of 1 % CNTs improves thermal stability. Consequently, a CNT concentration of 1.5 % is recommended.